Jews, Germans, and Allies : close encounters in occupied Germany - Grossmann, Atina 1950- (Princeton Univ. Press, 2007)
"Poor Germany": Berlin and the Occupation -- Gendered Defeat: Rape, Motherhood, and Fraternization -- "The Survivors were Few and the Dead were Many": Jews in occupied Berlin -- The Saved and Saving Remnant: Jewish Displaced Persons in the American Zone -- Mir zaynen do: Sex, Work and the DP Baby Boom -- Conclusion: The "Interregnum" Ends